2020
DOI: 10.1200/jco.2020.38.15_suppl.4044
|View full text |Cite
|
Sign up to set email alerts
|

TAS-116, an oral HSP90 inhibitor, in combination with nivolumab in patients with colorectal cancer and other solid tumors: An open-label, dose-finding, and expansion phase Ib trial (EPOC1704).

Abstract: 4044 Background: Regulatory T cells (Tregs) potentially induce the resistance of anti-PD1/PD-L1 inhibitors (A-PD1). TAS-116, a novel HSP90 inhibitor, enhanced antitumor immunity via reducing Tregs in vitro and in vivo. Combination of TAS-116 plus A-PD1 showed a superior tumor growth suppression compared with either treatment alone in vivo. Based on the above, we investigated safety and efficacy of TAS-116 in combination with nivolumab in patients with solid tumors. Methods: Enrolled patients received TAS-116 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The National Comprehensive Cancer Network (NCCN) guidelines have adopted TMB as the recommended test for patients with NSCLC receiving immunotherapy. Although the results in some clinical studies of RCC [15], HPV-positive HNSCC [13], and melanoma receiving anti-PD-1 after recurrence [16] showed that TMB alone also did not clearly distinguish responders and predict OS, it is still exciting that multiple studies in the 2020 American Society of Clinical Oncology (ASCO) meeting have confirmed the predictive value of TMB in immunization or combination therapy (KEYNOTE-061 study [17,18], CONDOR study [19], EAGLE study [20], EPOC1704 study [21], etc. ), consolidating its status of TMB as an independent predictor.…”
Section: Advances Of Multiple Predictive Biomarkers To Icis Efficacy (I) Tumor Genome and Neoantigen Biomarkersmentioning
confidence: 99%
“…The National Comprehensive Cancer Network (NCCN) guidelines have adopted TMB as the recommended test for patients with NSCLC receiving immunotherapy. Although the results in some clinical studies of RCC [15], HPV-positive HNSCC [13], and melanoma receiving anti-PD-1 after recurrence [16] showed that TMB alone also did not clearly distinguish responders and predict OS, it is still exciting that multiple studies in the 2020 American Society of Clinical Oncology (ASCO) meeting have confirmed the predictive value of TMB in immunization or combination therapy (KEYNOTE-061 study [17,18], CONDOR study [19], EAGLE study [20], EPOC1704 study [21], etc. ), consolidating its status of TMB as an independent predictor.…”
Section: Advances Of Multiple Predictive Biomarkers To Icis Efficacy (I) Tumor Genome and Neoantigen Biomarkersmentioning
confidence: 99%
“…TAS-116, another novel agent, is orally active and selective against cytoplasmic Hsp90. Although TAS-116 monotherapy shows limited antitumor effect [ 95 ], TAS-116 plus nivolumab, an immune checkpoint inhibitor, demonstrates an augmented treatment response against microsatellite-stable (MSS) CRC compared to TAS-116 monotherapy [ 96 ].…”
Section: Therapeutic Strategies Against P53 Mutantsmentioning
confidence: 99%
“…On one hand, TMB has been approved as a companion diagnostic biomarker, and multiple clinical trials have demonstrated its relevance to immunotherapy efficacy ( 13 15 ). Multiple studies presented at the 2020 ASCO meeting confirmed the predictive value of TMB in immunization or combination therapy, including KEYNOTE-061 study ( 16 , 17 ), CONDOR study ( 18 ), EAGLE study ( 19 ), and EPOC1704 study ( 20 ), consolidating TMB as an independent predictor. On the other hand, several investigators have noted that TMB is not a perfect predictor of response to anti-PD-1/PD-L1 therapy, such as in KEYNOTE-158 study ( 21 ) and RATIONALE-304 study ( 22 ).…”
Section: Introductionmentioning
confidence: 97%